2014
DOI: 10.1063/1.4901952
|View full text |Cite
|
Sign up to set email alerts
|

Self-focusing and frequency broadening of laser pulse in water

Abstract: An analytical model for the avalanche breakdown of water by an intense short laser pulse of finite spot size is developed. Initially, the laser undergoes self-focusing due to Kerr nonlinearity. As it acquires large intensity, it causes heating and avalanche breakdown of water. The plasma thus created on the laser axis causes nonlinear refraction induced defocusing of the laser. Thermal conduction tends to flatten the temperature profile and reduce the nonlinear refraction. The plasma density modification leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…[24] In the investigation of self-focusing and frequency broadening of laser pulse in water, the laser beam initially undergoes self-focusing due to Kerr nonlinearity and then nonlinear refraction takes place which causes the laser beam to defocus. [25] Also, it has been found that with increase of power density and control parameters lead to trapping of particle in the potential and hence strong focusing. [26] Laser pulse propagating in a plasma under plasma density ramp tends to become more focused.…”
Section: Introductionmentioning
confidence: 99%
“…[24] In the investigation of self-focusing and frequency broadening of laser pulse in water, the laser beam initially undergoes self-focusing due to Kerr nonlinearity and then nonlinear refraction takes place which causes the laser beam to defocus. [25] Also, it has been found that with increase of power density and control parameters lead to trapping of particle in the potential and hence strong focusing. [26] Laser pulse propagating in a plasma under plasma density ramp tends to become more focused.…”
Section: Introductionmentioning
confidence: 99%
“…Использование импульсов фемтосекундной длительности с высокой плотностью мощно-сти приводит к возникновению самофокусировки излучения и может вызывать оптический пробой [3]. Особенно актуален данный процесс при попадании фемтосекундного излучения на ткани глаза, на кото-рых происходит фокусировка излучения.…”
Section: Introductionunclassified